Importance of mushroom supplementation as a prebiotic amalgamation in fed diet of improvement of weight gain (WG) in Nile Tilapia, (Oreochromis niloticus) (Journal of Pharmaceutical Negative Results, 2023)
This examine become confirmed to look at impact of mushroom supplementation as a prebiotic compound in fed diets of enhancement of increase overall performance in Nile tilapia, (Oreochromis niloticus) on the aquaculture unit in laboratory. A general of fifty fishes (25 in keeping with water tank) with preliminary common frame weighted of 50.64 ± 0.0329 gram had been fed diets supplemented with 25% mushroom stalk experimental food plan (MSEF) and market available food plan (MAF) for seven weeks in cage system. During the assessment, the physico-chemical parameters of used water had been maintained normal range for optimal growth. The effects confirmed the first-rate very last weight gains (WG) become discovered with inside the fish fed supplemented with 25% mushroom stalk experimental diet were suggestively accelerated as compared with fish fed market available food plan.